Survival and Migration of Rock Ptarmigan in Central Scandinavia - Nilsen, Erlend B.; Moa, Pål F.; Brøseth, Henrik; Pedersen, Hans Chr.; Hagen, Bjørn R. (Frontiers in Ecology and Evolution, 2020)
In a world undergoing massive declines in the distribution and abundance of many wildlife species, documenting basic ecological characteristics is often needed to be able to understand and potentially mitigate current and future pressures. Species living in alpine areas might be particularly vulnerable to climate change, in part because they are less likely to be able to migrate to new suitable areas. Here we report from a two year case study of rock ptarmigan (Lagopus muta) in central Scandinavia. Ptarmigan were captured in winter (n=84), and fitted with radio collars. We estimated the natural survival from mid-winter to late summer to be 0.55 (SE: 0.07), with no distinct differences between juveniles and adults, sex, or between the two years. Natural survival through late winter (February – April) was estimated at 0.77 (SE: 0.05), survival trough breeding season May-July at 0.65 (SE: 0.08), and harvest mortality through the February winter harvest at 9% (SE: 3%). Moreover, we documented large scale movement from the wintering grounds before the breeding season in the spring. The longest recorded movement was 79.5 km, and the mean distance from the capture site for birds still in the sample in May-July was 20.3 (SD: 18) km. We discuss the implications of the results in terms of ongoing climate change.